Boundary Stabilization of the Wave Equation with Time-Varying and Nonlinear Feedback. (29th June 2014) - Tian, Jian-Sheng; Wang, Wei; Xue, Fei; Cong, Pei-Yong
Abstract : We study the stabilization of the wave equation with variable coefficients in a bounded domain and a time-varying and nonlinear term. By the Riemannian geometry methods and a suitable assumption of nonlinearity and the time-varying term, we obtain the uniform decay of the energy of the system.